The Internal Heterogeneity of Carbon Emissions in Megacities: A Case Study of Beijing, China - Zheng Wang; Kangkang Gu; Hu Yu (Atmosphere)
Cities are of wide concern to scholars due to their major share of global carbon emissions. Energy-related carbon emissions differ significantly among cities, especially megacities, due to regional heterogeneity in socioeconomic conditions. To analyze the differences in influencing factors on carbon emissions within megacities, and further target emission reductions, measures were developed. Beijing was selected to investigate influencing factor differences in the core zones, developing zones and ecological zones using the STIRPAT model on the county level. The results show the following: (1) Regional heterogeneity existed in Beijing in carbon emissions changes from 2010 to 2022. The carbon emissions of the core zones grew steadily and were demonstrated as a major part of Beijing. (2) There were variations in the influencing factors of emissions. Population size was the major driving factor of emissions in the core zones, while emissions in the developing zones and ecological zones were driven primarily by GDP per capita. Notably, urbanization promoted the increase in carbon emissions in the developing zones, but had a negative influence on emissions in the ecological zones. The energy intensity was the primary negative force of carbon emissions in the three zones. (3) The differences in population, economic scale, industrial structure and technological level lead to the heterogeneity of carbon emissions in Beijing. The three zones should formulate targeted emission reduction measures based on the primary factors of carbon emissions and their functional positioning.